Cerebral Infarction Related to Carmustine Wafers in Glioblastoma: A Case Report - Nakada, Mitsutoshi (NMC Case Rep J, 2014)
Implantation of carmustine-impregnated wafers (Gliadel(®)) into the tumor resection cavity has demonstrated a survival benefit for patients with malignant glioma. However, some precautions should be taken regarding Gliadel implantation. We report a case of a 63-year-old man with glioblastoma who was implanted with Gliadel after a left temporal lobe tumor had been removed, and who later developed vasospasm of the lenticulostriate artery close to the implanted Gliadel, leading to serious cerebral infarction. Therefore, the implantation of Gliadel in cases where important vessels run close to the resection cavity should be considered with great caution.